2018
DOI: 10.1088/1361-6641/aab535
|View full text |Cite
|
Sign up to set email alerts
|

Electrical response of electron selective atomic layer deposited TiO2−xheterocontacts on crystalline silicon substrates

Abstract: Integration of oxygen deficient sub-stoichiometric titanium dioxide (TiO 2−x ) thin films as the electron transporting-hole blocking layer in solar cell designs are expected to reduce fabrication costs by eliminating high temperature processes while maintaining high conversion efficiencies. In this paper, we conducted a study to reveal the electrical properties of TiO 2−x thin films grown on crystalline silicon (c-Si) substrates by atomic layer deposition (ALD) technique. Effect of ALD substrate temperature, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Though these designs have reached an advanced stage in the development of efficient c‐Si solar cells, there still exist several challenges such as thermal instability, strong parasitic light absorption by the utilized thin films, especially a‐Si:H due to its rather small band gap, and the used inevitable complicated deposition processes by PECVD followed by photolithography and/or laser steps. Recently, there has been a considerable attention to use alternative dopant‐free CSCs for c‐Si solar cells due to their unique work function values, considerably large band gap, simpler contact formation, and ease of production by simpler techniques 4–12 . These dopant‐free CSCs have shown to remove fundamental limitations associated with doped Si layers such as Auger recombination, parasitic light absorption, and free carrier absorption 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Though these designs have reached an advanced stage in the development of efficient c‐Si solar cells, there still exist several challenges such as thermal instability, strong parasitic light absorption by the utilized thin films, especially a‐Si:H due to its rather small band gap, and the used inevitable complicated deposition processes by PECVD followed by photolithography and/or laser steps. Recently, there has been a considerable attention to use alternative dopant‐free CSCs for c‐Si solar cells due to their unique work function values, considerably large band gap, simpler contact formation, and ease of production by simpler techniques 4–12 . These dopant‐free CSCs have shown to remove fundamental limitations associated with doped Si layers such as Auger recombination, parasitic light absorption, and free carrier absorption 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 tabulates the relevant electrical data for n-cSi, a-Si:H, and TiO x layers used in the simulation that have been extracted from the appropriate literature. 63,66,[68][69][70][71] The parameters for MoO x and defects states of a-Si:H have been extracted from our earlier reported works. 63 For physical device modelling of solar cells, it is pertinent to include relevant physical models in the simulation code that are needed to compute the essential output parameters of the studied devices.…”
Section: Tcad Modelling Of the Proposed Devicementioning
confidence: 99%
“…The electrodes of anode and cathode have been realized with silver (Ag) and aluminium (Al) contacts at the front and rear of the device, respectively. Table 1 tabulates the relevant electrical data for n‐cSi, a‐Si:H, and TiO x layers used in the simulation that have been extracted from the appropriate literature 63,66,68‐71 . The parameters for MoO x and defects states of a‐Si:H have been extracted from our earlier reported works 63 …”
Section: Tcad Modelling Of the Proposed Devicementioning
confidence: 99%
“…The electrical properties of TiO 2 thin films grown by atomic layer deposition (ALD) on crystalline silicon substrates were studied recently [17]. It was found that a heterojunction was formed between the deposited TiO 2 and silicon substrate demonstrating nonohmic and asymmetric current-voltage characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a heterojunction was formed between the deposited TiO 2 and silicon substrate demonstrating nonohmic and asymmetric current-voltage characteristics. Usually, TiO 2 is treated as an n-type semiconductor with a wide bandgap reaching 3.4 eV, 3.2 eV, 3.02 eV and 2.96 eV for amorphous, anatase, rutile and brookite phases, respectively [17,18]. Therefore, nondoped, high quality TiO 2 has a high resistivity and may serve as an insulator for capacitors [19,20].…”
Section: Introductionmentioning
confidence: 99%